Optimized coaxial focused electrohydrodynamic jet printing of highly ordered semiconductor sub-microwire arrays for high-performance organic field-effect transistors - Lu, Liangkun; Wang, Dazhi; Zhao, Zhiyuan; Li, Yikang; Pu, Changchang; Xu, Pengfei; Chen, Xiangji; Liu, Chang; Liang, Shiwen; Suo, Liujia; Liang, Junsheng; Cui, Yan; et al. (Nanoscale, 2023)
Patterning of semiconductor polymers is pertinent to preparing and applying organic field-effect transistors (OFETs). In this study, coaxial focused electrohydrodynamic jet printing (high resolution, high speed, and convenient) was used to pattern polymer semiconductors. The influence of the key printing parameters on the width of polymer sub-microwires was evaluated. The width decreased with increasing applied voltage, printing speed, and concentration of the polymer ink. However, the width increased gradually with increasing polymer ink flow rate. A regression analysis model of the relationship between the printing parameters and width was established. Based on a regression analysis/genetic algorithm, the optimal printing parameters were obtained and the correctness of the printing parameters was verified. The optimized printing parameters stabilized the width of the arrays to ca. 110 nm and imparted a smooth morphology. Additionally, the corresponding OFETs exhibited a high mobility of 2 cm 2 V −1 s −1 , which is 5× higher than that of thin-film-based OFETs. One can conveniently obtain high-performance OFETs from ordered sub-microwire arrays fabricated by CFEJ printing. OFETs based on printed highly ordered and controllable sub-microwires (∼110 nm) exhibited extra high mobility (∼2 cm 2 V −1 s −1 ).